2007
DOI: 10.1179/joc.2007.19.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6-Azacytidine on the Course of Experimental Adenoviral Infection in Newborn Syrian Hamsters

Abstract: Adenoviral infection is a serious human pathology leading to respiratory, gastrointestinal and ocular disorders and epidemic outbreaks, especially in children's groups. Here we present the results from an investigation of anti- adenoviral effect of 6-azacytidine (6-AC) both in vitro and in vivo. The selectivity index of 6-AC for adenovirus type 5 in HEp-2 cells was 374, the 50% effective concentration was 0.5 mg/ml. For in vivo investigations we developed a model of disseminated adenoviral infection in newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
1
14
0
3
Order By: Relevance
“…Several animal models have been proposed that are to some extent permissive for human Ad replication, including cotton rats (30,31), pigs (32), dogs (33), and Syrian hamsters (34)(35)(36). However, these studies did not address replication of Ad under conditions of immunosuppression, as is observed in transplant patients.…”
mentioning
confidence: 91%
“…Several animal models have been proposed that are to some extent permissive for human Ad replication, including cotton rats (30,31), pigs (32), dogs (33), and Syrian hamsters (34)(35)(36). However, these studies did not address replication of Ad under conditions of immunosuppression, as is observed in transplant patients.…”
mentioning
confidence: 91%
“…All three carbon atoms in this molecule are bonded to one, two or three electronegative partners, and so have high binding energies. In 6-azacytidine, the peak A at about 288.3 eV corresponds to the same peak in 6-azacytosine, assigned to the urea carbon C (2) , and with C (4) and C (5) at 0.5 and 1.9 eV lower binding energy respectively. 6-azacytidine contains 8 carbon atoms in total, and these mainly contribute to the strongest peak C. The overall agreement between theory and experiment is satisfactory.…”
Section: (I)mentioning
confidence: 78%
“…The shifts of the other two core levels, C (4) and C (6) , are attributed to indirect effects of hydrogen bonding and chemical interaction with the surface. The N 1s and C 1s spectra of vacuum deposited cytosine are very similar for Au(111) and (110), although the O 1s spectrum shows a significant difference in energy between the two surfaces.…”
Section: Core Level Spectra Of Cytosinementioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] More recent research on antiviral properties of 6-azaСyd has demonstrated its high activity relative to human AdV in vitro and in vivo systems. [8][9][10][11][12][13] In cell cultures, the anti-adenoviral effect of 6-azaСyd was expressed by inhibiting the formation of virus-specific intranuclear DNA-containing inclusion bodies, the synthesis of viral proteins and infectious virus. [12,14] The application of 6-azaСyd on a model of disseminated AdV infection in newborn Syrian hamsters led to significant decrease of virus titer and shortening of the time of virus clearance in organs.…”
Section: Introductionmentioning
confidence: 99%